RASIO KEUANGAN TERHADAP LABA PADA PERUSAHAAN - Rohana Sitanggang; Yacob Viviandi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
Financial ratios describe a relationship between a certain number with another number, and explain to analysts about the good or bad circumstances or the financial position of a company, if the ratio is compared with the comparative ratio is used as a standard. The purpose of this study was to determine the influence of financial ratios to profit in the company Persero Batam. The method used is associative method, which is to determine the relationship between two or more variables. The analysis technique used is multiple regression analysis with the first process the data using quantitative methods, followed by horizontal analysis, classic assumption test (normality test, multicollinearity, heteroscedasticity test, and test autokorelaso), and the correlation coefficient of determination, t test, and F test